2017
DOI: 10.1038/s41598-017-01594-7
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic transport in soil by earthworms

Abstract: Despite great general benefits derived from plastic use, accumulation of plastic material in ecosystems, and especially microplastic, is becoming an increasing environmental concern. Microplastic has been extensively studied in aquatic environments, with very few studies focusing on soils. We here tested the idea that microplastic particles (polyethylene beads) could be transported from the soil surface down the soil profile via earthworms. We used Lumbricus terrestris L., an anecic earthworm species, in a fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
258
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 643 publications
(293 citation statements)
references
References 25 publications
1
258
0
4
Order By: Relevance
“…Once in terrestrial ecosystems, plastics accumulated in surface soils and can be ingested by soil-dwelling organisms (Rillig, 2012;Rillig, Ingraffia, & Souza Machado, 2017). Empirical data indicate that plastics are incorporated into earthworm casts (Huerta Lwanga et al, 2017), and also that polyethylene microbeads (0.71-2.8 mm) reach down into the subsurface through earthworm burrows (Rillig, Ziersch, & Hempel, 2017). The concentration of plastic in soils varies; river floodplains across Switzerland revealed relatively low concentrations of microplastics (0-55.5 mg/kg, Scheurer & Bigalke, 2018), but more heavily contaminated industrial soils (300-67,500 mg/ kg) have been observed from samples collected in Australia (Fuller & Gautam, 2016).…”
Section: Terrestrial Systemsmentioning
confidence: 99%
“…Once in terrestrial ecosystems, plastics accumulated in surface soils and can be ingested by soil-dwelling organisms (Rillig, 2012;Rillig, Ingraffia, & Souza Machado, 2017). Empirical data indicate that plastics are incorporated into earthworm casts (Huerta Lwanga et al, 2017), and also that polyethylene microbeads (0.71-2.8 mm) reach down into the subsurface through earthworm burrows (Rillig, Ziersch, & Hempel, 2017). The concentration of plastic in soils varies; river floodplains across Switzerland revealed relatively low concentrations of microplastics (0-55.5 mg/kg, Scheurer & Bigalke, 2018), but more heavily contaminated industrial soils (300-67,500 mg/ kg) have been observed from samples collected in Australia (Fuller & Gautam, 2016).…”
Section: Terrestrial Systemsmentioning
confidence: 99%
“…In addition to simply moving microplastics, biotic activities may also place them in pedological contexts they would rarely if ever otherwise occupy. Earthworms incorporate microplastics into their casts and burrow walls (Huerta Lwanga, Gertsen, et al, ; Huerta Lwanga et al, ; Huerta Lwanga, Mendoza Vega, et al, ; Prendergast‐Miller et al, ; Rillig, Ziersch, et al, ). These casts and burrows comprise a unique microhabitat that soil ecologists term the drilosphere (Andriuzzi, Bolger, & Schmidt, ; Sharma, Chandra, & Kanta, ).…”
Section: Faunal Effects: Dispersal and Positioningmentioning
confidence: 99%
“…Abiotic movement of microplastics through the soil matrix may be altered through biological activities. Earthworm burrowing increases soil porosity and water infiltration rates (Bottinelli et al, 2015;Capowiez et al, 2009;Lavelle et al, 1997), which may enable deeper water-assisted spread of microplastics into the soil profile (Rillig, Ziersch, & Hempel, 2017;Yu et al, 2017). Plant roots can also move soil organisms as they grow and create channels for additional movement (Demarta, Hibbard, Bohn, & Hiltpold, 2014;Dighton, Jones, Robinson, & Beckett, 1997) and thus may also facilitate passive microplastic dispersal deeper into the soil profile.…”
Section: Faunal Effec Ts: D Is Per Sal and P Os Itioningmentioning
confidence: 99%
See 2 more Smart Citations